New sealing material for drainage operations - H Li; SS Guo; DS Yuan (Functional Materials, 2018)
A new sealing material for the drainage operations from pulverized coal was investigated. Its microstructure and strength characteristics are determined. Evaluation of the quality of the test material for hermetic sealing of holes was verified in a coal mine. Experiments have shown that the concentration of drainage gas in the wellbore, which is sealed with sealing material from the pulverized-hole, is higher than when using an expensive cement material (82.50% vs. 69.65%).